Edukasi Skrining COVID-19 pada Program Teknologi Reproduksi Berbantu di Era Pandemi COVID-19 - Uki Retno Budihastuti; Abdurahman Laqif; Eriana Melinawati; Teguh Prakosa; Hermawan Udiyanto; Heru Priyanto; Darto Darto; Affi Angelia Ratnasari; Asih Anggraeni (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
In the era of the coronavirus disease 2019 (COVID-19) pandemic, COVID-19 screening education is essential for the general public, especially for those who undergo assisted reproductive technology (ART) programs. Understanding the preventive measures and precautions of COVID-19 during the treatment process is necessary. Health care staff must also understand the importance of proper COVID-19 screening and control measures. This educational activity is in the form of a YouTube live streaming program that can be followed by the general public, including infertile couples who want to know about infertility, examination procedures, COVID-19 screening guidelines, and the TRB program. Education about COVID-19 screening can minimize stigma and enhance public confidence in the screening procedures. The results of this educational delivery make the general public, especially couples who will undergo the ART program, ready and have the ability to undergo COVID-19 testing, services, and screening. In addition, by providing education and implementing effective screening, we can work together to combat the COVID-19 pandemic and ensure that people receive quality and safe health services.